2014
DOI: 10.1097/bcr.0b013e3182aa7143
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Silver-Loaded Nanofiber Dressings in Candida albicans–Contaminated Full-Skin Thickness Rat Burn Wounds

Abstract: In this experimental study, the effects of nanofiber dressings containing different forms of silver on full-thickness rat burn contaminated with Candida albicans was analyzed. A full-thickness skin burn was formed on a total of 32 Sprague-Dawley rats. After the burn wound was seeded with a 10 colony-forming units/ml standard strain of Candida albicans ATCC90028, the animals were divided into four groups. The effects of topical silver sulfadiazine and two recently designed nanofiber dressings containing nanosil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Their results showed that the composite system exhibited antibacterial activity against Gram‐negative Escherichia coli and Gram‐positive Staphylococcus aureus . Silver‐loaded dressings have also been reported as effective against nonbacterial targets, including fungi .…”
Section: Drug‐containing (Delivery) Dressingsmentioning
confidence: 99%
“…Their results showed that the composite system exhibited antibacterial activity against Gram‐negative Escherichia coli and Gram‐positive Staphylococcus aureus . Silver‐loaded dressings have also been reported as effective against nonbacterial targets, including fungi .…”
Section: Drug‐containing (Delivery) Dressingsmentioning
confidence: 99%
“…Silver has also been found to be toxic against nonbacterial targets such as fungi. Nanofiber dressing loaded with 1% silver is used to treat fungi‐contaminated burn wounds 105 . However, the results were not statistically significant, authors presumed that it was due to the low concentration of silver loaded in the dressing compared with commercial products in the market.…”
Section: Bioactive Moleculesmentioning
confidence: 99%
“…Silver-coated dressings and Nystatin have proven to be effective treatments (Acar et al, 2011 ). Electrospun SSD-containing nanofiber dressings were also shown to be effective against C. albicans infected burn eschar (Ciloglu et al, 2014 ). In many burn centers, systemic administration of Amphotericin B is used when invasive fungal infection is suspected; however, systemic administration of Amphotericin B is associated with a dose-dependent nephrotoxic effect (Hamill, 2013 ).…”
Section: Inflammationmentioning
confidence: 99%